Effects of physical activity on subjective well-being: the mediating role of social support and self-efficacy - Guo, Siqiang; Fu, Huaying; Guo, Kelei (Frontiers in Sports and Active Living, 2024)
Objective Subjective well-being is an essential component of college students' mental health, and the purpose of this study was to investigate the relationship between physical activity and subjective well-being among college students and to examine the mediating role of social support and self-efficacy between the physical activity and subjective well-being. Methods This study utilized a cross-sectional design with a stratified whole group sample of 989 college students (Mage = 19.65 years, SD = 1.1) from three universities in Guangdong Province, China, and used the Physical Activity Scale, Subjective Well-Being Scale, Social Support Scale, and Self-Efficacy Scale for data collection. In this study, SPSS 26.0 was used for descriptive statistical analysis and correlation analysis of the collected data. Harman's one-way method was used to test for common method bias. Results (1) Physical activity, subjective well-being, social support and self-efficacy were significantly correlated with each other. Among them, physical activity was significantly and positively correlated with subjective well-being (r = 0.36), physical activity directly predicted subjective well-being (β = 0.125, t = 3.992, p < 0.01). (2) Physical activity positively predicted social support (β = 0.386, t = 12.505, p < 0.01) and self-efficacy (β = 0.358, t = 11.793, p < 0.01), social support significantly positively predicted subjective well-being (β = 0.332, t = 11.370, p < 0.01) and self-efficacy (β = 0.254, t = 8.744, p < 0.01), self-efficacy significantly and positively predicted subjective well-being (β = 0.255, t = 8.251, p < 0.01). (3) Not only did social support and self-efficacy play an independent mediating role between physical activity and subjective well-being, but social support and self-efficacy played a chain mediating role between physical activity and subjective well-being. Conclusion This study enriched the theoretical guidance for physical activity in promoting college students' subjective well-being. In the practical teaching of promoting college students' subjective well-being, in addition to paying attention to stimulating physical activity, special attention should be paid to the promotion of social support and self-efficacy.